Reingeniería de procesos de la cooperativa de ahorro y crédito Yuyarik de la ciudad de Ambato - Capuz Yugcha, Segundo Pablo (2015)
This work is about Process Reengineering Cooperative "Yuyarik", whose main objective is to make a proposal reengineering processes that involve an improvement in the quality of services received by members of the Cooperative "Yuyarik" city of Ambato. For removal of the literature review through bibliographical research could expand concepts and definitions. In addition to the inductive, deductive, analytical, synthetic and descriptive method could analyze the information gathered through interviews with the manager of the cooperative and the surveys of 20 employees and 359 partners, of which data were obtained to learn about the current structure, the services they provide and the key processes performed in the Cooperative later with the information gathered was found that there are shortcomings in the process of granting loans, account opening and customer service are also identified , processes must be redesigned; and that directly affect the welfare of members, as evidenced by 143 respondents equivalent to 52% of the partners (question 7), just as 115 partners believe that should improve the infrastructure and environment of the Cooperative (question 9). With the collected information and then analyzing it is concluded that re-engineering and restructuring is implemented in the aforesaid processes; recommending to the finance these processes work in a pleasant, comfortable customer they like and feel attracted to bid quality service and be a competitive entity